2015
DOI: 10.1111/camh.12113
|View full text |Cite
|
Sign up to set email alerts
|

Review: Effectiveness of mindfulness in improving mental health symptoms of children and adolescents: a meta‐analysis

Abstract: Background: Mindfulness-based interventions (MBIs) are increasingly used in the management of various mental health disorders in children and adolescents. However, there is limited evidence about the efficacy of various interventions used. Method: A systematic review was performed to examine the effects of different MBIs on mental health symptoms and quality of life in both clinical and nonclinical samples of children and adolescents using data from only randomized control trials. The studies were also assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
132
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(160 citation statements)
references
References 43 publications
6
132
2
6
Order By: Relevance
“…Mindfulness interventions, which include yoga and meditation, have been found to increase youth resilience and self-regulation of stress, emotions, and behavior. [64][65][66][67] The federal government took an important step toward reinforcing trauma-informed approaches in schools through the Every Student Succeeds Act (ESSA), signed by President Barack Obama in December 2015. 68 This bipartisan measure reauthorized the United States' national education law.…”
Section: Evidence-based Interventionsmentioning
confidence: 99%
“…Mindfulness interventions, which include yoga and meditation, have been found to increase youth resilience and self-regulation of stress, emotions, and behavior. [64][65][66][67] The federal government took an important step toward reinforcing trauma-informed approaches in schools through the Every Student Succeeds Act (ESSA), signed by President Barack Obama in December 2015. 68 This bipartisan measure reauthorized the United States' national education law.…”
Section: Evidence-based Interventionsmentioning
confidence: 99%
“…Many studies have documented positive effects of mindfulnessbased therapies on mental and physical health [6,7] including improved quality of life [8] and well-being [5,9], and a reduction in psychiatric symptoms [10]. Even short interventions have found that increased mindfulness effectively decreases anxiety and stress [11,12].…”
Section: Mindfulness Backgroundmentioning
confidence: 99%
“…This herb induces cytochrome p450, so be aware of the potential adverse effects (similar to other SSRIs and Sd. Serotonergic, among others) and interactions with other medicines, in this sense it is important to warn the Adolescents women use this herb in conjunction with oral contraceptives, which could have a decrease in their effectiveness 24,25 .…”
Section: Mood Disordersmentioning
confidence: 99%